Highly compliant and low strain hysteresis sensory electronic skins based on solution processable hybrid hydrogels. Issue 5 (14th January 2021) - Wang, Mingcheng; Zhou, Hongwei; Jin, Xilang; Liu, Hanbin; Ma, Aijie; Yan, Hanbing; Chen, Lin; Chen, Weixing
Abstract : Hydrogels with compliance and low hysteresis are developed. Based on the hybrid hydrogels, sensory electronic skins with outstanding recyclability and sensitivity are fabricated. Abstract : Compliance and low strain hysteresis are of great importance for wearable devices and electronic skins, but it is still a challenge to obtain materials with high compliance, low strain hysteresis and sensing ability for electronic skins. In this work, we have achieved highly compliant and low strain hysteresis sensory electronic skins (SESs) utilizing solution processable hybrid hydrogels. The hybrid hydrogels are constructed by incorporating polyaniline (PANI) into poly(vinyl alcohol) (PVA). By regulating the contents of PVA and PANI, the elastic modulus of the PVA/PANI hybrid hydrogels can be tuned in the range of 15.7–154.4 kPa, which covers the elastic modulus of human soft tissue (≈30 kPa). The PVA/PANI hybrid hydrogels also achieve low strain hysteresis and exhibit outstanding recovery during the cyclic loading–unloading process. In such hydrogels, PANI works as the conductive component and contributes to the conductivity of the hybrid hydrogels (13.3 S m −1 ). Further investigations reveal that the compliant SESs possess high sensitivity (GF = 4.28), outstanding stability (>1000 cycles) and low response time (250 ms). Because of the fully physically cross-linked structure, the hydrogels in SESs are completely solution processable and can be regenerated. By introducing glycerol into the hybrid hydrogels, the flexibility of SESs can be kept at least for one week and the sensing ability is also well maintained. Finally, we demonstrate that SESs exhibit reliable sensing ability in monitoring representative human movements, such as joint bending and swallowing.